INTEGRATED APPROACH IN NUTRIENT MANAGEMENT OF SUMMER GREEN GRAM - P. K. TYAGI; A. K. UPADHYAY; R. S. RAIKWAR (The Bioscan, 2014)
A field experiment on integrated nutrient management practices for augmenting the productivity of summer green gram (Vigna radiata L.) was carried out in clay loam soil at Research Farm, J.N.K.V.V., College of Agriculture, Tikamgarh (Madhya Pradesh), India for two consecutive years during summer 2012 and 2013. The experiment was laid out in randomized block design replicated thrice with 10 different nutrient management treatments. The results revealed that integration of 100% RDF + Vermicompost @ 1.0 t/ha + Rhizobium resulted into significantly greater plant height (52.3 cm), number of primary branches/plant (5.8), higher total dry matter accumulation (19.6 g/plant)at harvest, maximum leaf area index (3.0) at 45 DAS, number of pods/plant (13.5), number of seeds/ pod (10.6), 1000 seed weight (36.4 g) and seed yield (1081.1 kg/ha)in comparison to other nutrient management treatments. Application of 100% RDF + Vermicompost @ 1.0 t/ha + Rhizobium also recorded higher N, P and K uptakes by seed (40.3, 4.10 and 9.73 kg/ha, respectively) and stover (32.6, 4.33 and 10.8 kg/ha, respectively) as well as total uptakes (72.9, 8.43 and 20.5kg/ha, respectively) as compared to rest of treatments. Hence, it can be concluded that the application of 100% RDF + Vermicompost @ 1.0 t/ha + Rhizobium would be useful to enhance the productivity of summer green gram. The conjunctive use of organic manures and inorganic fertilizers alongwith biofertilizer may be suggested for higher productivity along with overall betterment of summer green gram.